Risk and determinant factors for obstructive sleep apnea in patients with epilepsy - Venturi,Monique (2011)
OBJECTIVE: To evaluate the prevalence of risk of having obstructive sleep apnea (OSA) and its determinants in patients with epilepsy (PE). METHOD: 98 adult PE were prospectively screened for risk of OSA by Berlin questionnaire. Data was also collected about excessive daytime sleepiness, depression, anxiety, clinical and socio-demographic characteristics. RESULTS: The PE main characteristics: 59-men/39-women, mean age=39.97, SD=12.3, range 18-66. The prevalence of the risk of OSA was 55.1% (CI 95%, 0.45-0.65). The high risk for OSA was related with body mass index (BMI) (p=0.000), neck circumference (NC) (p=0.000), arterial hypertension (AH) (p=0.000), and anxiety (p=0.006), without relationship with number of seizures, number of antiepileptic drugs, age or depression. The NC was statistically significant regarding risk of OSA, mainly in men. CONCLUSION: We found a high risk of OSA in this sample. The main implicated measures were the large NC, high BMI and anxiety. The anthropometric variables were more relevant than those related to epilepsy itself and similar to those of the general population.